Gramíneas no cerrado brasileiro : uma história ambiental das transformações das paisagens em Goiás a partir do século XIX - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The following work has its enphasis in the study of the transition between the pastures considered native of the Cerrado Biome and the arrival of the most common exotic grasses, over the XIX century of the Goiás State. We search to historicize the process of introduction of the exotic african grasses that came along with the colonizer in its way of the land occupation procedure of the central area of Brazil, some know examples, the capim-gordura, Melinis minutiflora P. Beauv., the capim-jaraguá, Hyparrhenia rufa (Ness) Stapf. With this, we try to undertand those pastures transformations and its involvement in the Cerrado phyto- physiognomy, as well, the human relations changes resulting from this scenario. We stick to the anthropogenic actions in the environment, also, the human relationship changes caused by the environment. This approach came from interdisciplinary studies, and we used the environmental history as the base of this study, we work with Social Science and Natural Science. Given the dynamic and the historicize of men and women in this environment, we look to the livestock and the Goiana Economy in the XIX century; by this means, we discuss the concept of the livestock frontier developed by McCreery (2006), on which Goiás fit as the "a fronteira da fronteira" ("the frontier of the frontier"), related to the province configuration isolated and remotest of Brazil and having the livestock as its main commercial product during this time.
Keywords: Gramíneas no Cerrado; Fronteira do Gado; História Ambiental; Grasses in Cerrado; Livestock Frontier; Environmental History; CIENCIAS HUMANAS::GEOGRAFIA; GEOGRAFIA FISICA::GEOECOLOGIA; ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS